From Race Crisis to Race Celebration: Online Body Politics and the Alvin Ailey American Dance Theateri - Alexandru Maria-Sabina Draga (American, British and Canadian Studies Journal, 2022)
Throughout the history of the United States, there have been many critical times associated with racism. When other forms of crisis overlap the existing ones – as the Covid-19 pandemic – even more challenges appear, calling for a more complex artistic response. The Alvin Ailey American Dance Theater is well known across the United States and the world not only through their innovative ballet style (which builds on classical choreography and enriches it with creatively processed blues, jazz, and Afro-Caribbean tones), but also through what Thomas F. DeFrantz calls Alvin Ailey’s “embodiment of African American culture” in the subtitle of his book (Dancing Revelations, 2004). This essay looks at Ailey Theater’s politics of the dancing body, with a focus on recent productions included in the Ailey All Access online project, meant to replace a Fall 2021 United States tour that could not take place because of the pandemic. I will argue that the company’s choreographic overcoming and even beautifying sorrow through dance expands Ailey’s healing narrative about African American history to the Covid-19 pandemic. Their recent projects propose a desirable post-racist world, in which those who have been through much sorrow can support those who have been through less, and thus promote a politics of human togetherness, hope, and reconstruction.